Pengaruh Lama Penggunaan Kb Suntik (DMPA) Terhadap Kadar Low Density Lipoprotein (LDL-C) - Solihah, Riyadatus; Umar, Rizal (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2022)
DMPA may cause increased lipophysis or hydrolysis. Then the large amount of free fatty acids is carried to the liver, causing increased triglyceride synthesis and VLDL secretion. In the state of insulin resistance VLDL becomes increased in circulation and can cause an increase in Low Density Lipoprotein (LDL), LDL is mostly formed from VLDL. The purpose of this study was to determine the effect of injectable birth control (DMPA) on Low Density Lipoprotein (LDL) levels. The research method used in this study is analytic with a cross sectional approach. The technique used was purposive sampling in a population of 60 respondents and a sample of 24 respondents in women who used DMPA injectable birth control in Ponkesdes Fariyah.S.ST. The results obtained from 24 samples showed as many as 12 samples (50%) using DMPA injections above 3 years had higher LDL cholesterol levels compared to 12 samples (50%) using DMPA injections above 5 years. The results of statistical tests conducted with the Independent Samples Test test obtained a significant value of 0.793 (p ≥ 0.05) so it can be concluded that there is no difference in LDL-cholesterol levels in the use of injectable birth control for more than 3 years and more than 5 years. For women who use DMPA injectable birth control, it is advisable to check LDL levels more often so that the LDL levels in the blood can be known.